Risk factors for violence against women by the spouse - Fabián Árias, Eugenia (2020)
The objective of the present work was to carry out a bibliographic review on the risk factors of violence against women by her spouse, considering that risk factors are characteristic or circumstances that are likely to develop some effect and / or adverse consequences. The researches that has been carried out on risk factors is analyzed, the results of this review allow us to conclude that violence against women is historical and has remained, and remains, in a large percentage hidden, because most do not denounce for fear of further violence. . The risk factors for violence against women to occur is multifactorial due to the characteristics of family dynamics in each country. The results of the studies show that the risk factors for violence against women are found at the macro-structural level; exosystem, and microsystem. In addition, there are various theories and models that explain the factors that are associated with violence against women.   DOI: https://doi.org/10.31876/sl.v3i1.67